CTEX CPAP versus Conventional CPAP in Managing COVID-19 related Respiratory Failure: Experience from a Hospital - Akhtaruzzaman, AKM; Kamal, Md Mostafa; Bhowmick, Dilip Kumar; Islam, Md Shafiqul; Mithu, Selim Musa (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: Continuous positive airway pressure (CPAP) is the preferred form of noninvasive ventilatory support in the management of type 1 respiratory failure in COVID-19 patients with a pure failure of oxygenation only. Limiting the inherent disadvantages, the improved and enhanced CTEX CPAP device may benefit the patients. Objective: To evaluate the clinical effectiveness of a new novel continuous positive airway pressure (CPAP) device CTEX in managing COVID-19-associated type 1 respiratory failure. Methods: This open-label, double cross-over, non-inferiority trial was conducted among COVID-19-positive patients with respiratory failure who required oxygen supplementation and were admitted to the intensive care unit (ICU), under Department of Anaesthesia, Analgesia and Intensive Care Medicine, Bangabandhu Sheikh Mujib Medical University (BSMMU) Hospital, Dhaka, Bangladesh, between August 2020 and January 2021. A total of 39 patients with confirmed positive COVID-19 receiving standard CPAP (10-16cm of water) and entrained oxygen (2-15 L/ minute) and having peripheral oxygen saturations (SpO2) <94% were included in this study. Patients were given standard CPAP for 1 hour followed by CTEX CPAP for 12 hours and then switched back to standard CPAP for 1 hour. The primary outcome measure was the evaluation of oxygen saturation (SpO2) over 12 hours, which was measured hourly across 11 hours starting at T0 for the initial value and ending at T11 for the final value. Results: The mean age of the patients was 60.25±11.70 years; male to female ratio was 3.3:1. Most of the patients 21(54%) had SpO2 of 80-90% on admission. The average respiratory rate was 28.15±1.42 breaths per minute. SpO2 before and after applying CTEX CPAP were observed 88% (ranged between 81% and 94%) and 95% (ranged between 91% and 100%) respectively. There was a significant improvement in SpO2 and the value was increased over time and then plateaued. Conclusion: CTEX CPAP device was found to be significantly better at oxygenation for the treatment of COVID-19 patients with type 1 respiratory failure. International Journal of Human and Health Sciences Vol. 09 No. 01 Jan’25 Page: 42-47